Trade-Related Illicit Financial Flows in Southeast Asia: Evidence from Extractive and Agricultural Commodities in Laos - Viriyasack Sisouphanthong; Latdaphone Banchongphanith; Sthabandith Insisienmay; Latdavanh Songvilay (Revue Internationale de Politique de Développement)
The Association of Southeast Asian Nations (ASEAN) has emerged as one of the fastest growing collective economies in Asia. This fast growth is, however, accompanied by various challenges, including the trade-related illicit financial flows (IFFs) that deplete the tax revenues of the Association’s Member States. This chapter aims to shed light on the status of the trade-related IFFs present in the scale of trade mispricing that occurs between the ASEAN community and its global trade partners. To better interpret its findings, the chapter provides a legal framework analysis that highlights gaps in efforts to address these financial challenges in the region. Notwithstanding these gaps, certain Member States with substantial non-tax revenue streams have reduced reliance on conventional taxation, allowing for unique fiscal strategies. A comparative analysis of readiness among ASEAN Member States, meanwhile, reveals disparities, with advanced economies demonstrating robust legal systems while developing countries face challenges in implementing complex tax regulation. The chapter also examines the vulnerability of countries that lack robust legal frameworks, using the Lao People’s Democratic Republic (PDR), a landlocked, least-developed country dependent on extractive resources and agricultural exports, as a case study. By estimating the magnitude of trade mispricing of selected mineral and agricultural product exports, the chapter tries to present the consequential impact on potential tax revenue erosion and the economy. Its findings underscore the critical role of legal foundations in addressing the issue of IFFs, including the importance of transfer pricing rules in preventing trade mispricing. Based on these findings, this study encourages less economically developed, tax-revenue-reliant nations like Lao PDR to continue developing a transparent legal system, improve current trade databases, and enhance cooperation with international bodies. This study also suggests such countries explore alternative methods, such as simplified approaches, of estimating tax liabilities and curbing trade mispricing.